Changes in the Coastal and Fishery Resources and Local Ecological Knowledge (LEK) About Fishery Practices as Perceived by the Fisher Folks in Selected Coastal Municipalities of Zambales, Philippines - Paz-Alberto, Annie Melinda; Parico, Oliva B.; Alberto, Roann P.; Ponce, Carl Dionelle; Juganas, Daryl A. (Silliman Journal, 2022)
This study was conducted to carry out a perception study on the changes in the coastal and fishery resources and the local ecological knowledge (LEK) about fishery resources and practices in selected municipalities in the province of Zambales. The researchers conducted a survey interview with the fisher folks living along the coastal areas to assess their knowledge and perception of the coastal and fishery resources in the four coastal municipalities, namely Palauig, Masinloc, Candelaria, and Sta. Cruz in Zambales, Philippines and documented their local ecological knowledge concerning fishery resources. The majority of the fisher folks responded that there was already a decrease in fish population in the coastal and fishery resources, while half replied that the seashore and coastline aesthetic appearances had been destroyed. However, there were no changes in mangrove and seagrass ecosystems. Instead, most of them alleged that the main reasons for these problems are human activities and overexploitation. The local ecological knowledge (LEK) is still rich and varied among the different coastal communities considering their cultural differences, practices, and topography. However, results revealed that most of the documented LEK focused on the fishing practices in coastal and fishery resources for fishing serves as their main livelihood. Only half of those interviewed from Palauig, Candelaria, and Masinloc, and Sta. Cruz followed and observed their old ways of fishing, such as using payao, sunggapong, and kawil, while some of them implemented the modified ways like hila-hila and lambaklad, among others. LEK in fishing practices and coastal and fishery resources are now very scarce, and only a few fishermen are well informed of this traditional knowledge. Also, it seems that these practices have been modified, revised, and converted by the younger generation of fishers. These traditional knowledge, systems, and practices are at a declining rate due to the continuing loss of interest of the young fisher folks. In the face of ongoing environmental changes, and cultural and biological diversity, the coastal and fishery resources are likely to be severely impacted. Moreover, local resilience capacities suffer from this loss of traditional and local ecological knowledge. Thus, if LEK will continue to be harnessed, adapted, and practiced by the local fishers, this could be a holistic management tool in conserving fishery and coastal resources in the changing environmental conditions.